The association between body mass index (BMI), body fat percentage and circadian rhythm disturbances among undergraduate students in Universiti Sains Malaysia, Kubang Kerian - Ropi, Raihana Basirah Mat (Universiti Sains Malaysia, 2025)
Body mass index (BMI) and body fat percentage are important indicators of nutritional status. Despite their importance, many still experience issues related to BMI and body fat that may be associated with circadian rhythm disturbances, especially among university students. The objective of this research was to study the association between BMI, body fat percentage, and circadian rhythm disturbances among undergraduate students in Universiti Sains Malaysia (USM), Kubang Kerian. This study was a cross-sectional study conducted on a total of 125 undergraduate students in Universiti Sains Malaysia, Kubang Kerian by using a self-administered online questionnaire. The subjects in this study were chosen using a simple random sampling and the data analysis was analysed using the SPSS version 29.0 software. The association between BMI, body fat percentage, and circadian rhythm disturbances was tested using Pearson’s Chi-Square test. Among the analyses, one of the six chrononutrition behaviours, evening latency, had a statistically significant association with BMI (p = 0.002). However, no significant association was found between body fat percentage and any of the six chrononutrition behaviours. In conclusion, this study suggests that efforts are required to promote better circadian rhythm management among university students to support healthy BMI and body fat percentage status